Penggunaan Trichoderma sp. yang Ditambahkan pada Berbagai Kompos untuk Pengendalian Penyakit Layu Tanaman Stroberi (Fragaria sp.) - LUTFI SURYAWAN; GUSTI NGURAH ALIT SUSANTA WIRYA; I PUTU SUDIARTA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
The Usage of Trichoderma sp. That Added Into A Variety of Compost For The Control Of Wilt Desease In Strawberries (Fragaria Sp.) The research of utilizationTrichoderma sp. that added into a some kind of composts for the control of strawberries wilt desease had been done on December 2016 until May 2017. The purpose of this research is to find the best compost that combined with Trichoderma sp. for the control of wilt disease in strawberry. This research was carried out two stages that is in the laboratory to get the best antagonist microbes and in the greenhouse to get the best compost as an antagonistic microbial medium to controlling wilt disease in strawberries plants. The result of this research showed that the antagonistic microbial that has the highest percentage of inhibitory activity against the wilt disease pathogen was the antagonistic microbial from the rhizosphere of clove plants by 86 %. It was suspected that the antagonistic microbial is Trichoderma sp. Greenhouse research showed the lowest percentage of disease found in the compost treatment of antagonistic microbial + goat manure is 0%. The best compost as the carrier of the antagonistic microbial (Trichoderma sp.) is the compost that made from goats manure.